Investor protection in indonesia: a legal analysis of securities regulation - Emmi Rahmiwita Nasution (Institute of Computer Science (IOCS), 2023)
One of the most important foundations for building trust, drawing money, and maintaining the stability of the financial system is investor protection. The efficacy of investor protection mechanisms within the securities regulatory system is of utmost importance in the context of Indonesia, a nation undergoing swift expansion in its financial industry. This study undertakes a thorough examination of Indonesia's securities laws, breaking down the regulatory structure, assessing how well it is being applied in practise, and pinpointing the system's advantages and disadvantages. To produce a comprehensive assessment, the research combines a number of techniques, such as surveys, in-depth interviews with important parties, and legal analysis. The results show that although Indonesia has a thorough legal system, there are still issues with investor education, dispute resolution, and enforcement. The findings highlight the necessity of enhanced implementation and regulatory reform in order to strengthen investor protection. This research has ramifications that go beyond national boundaries and impact Indonesia's appeal to global investors. In the end, our study adds to the continuing discourse on market integrity and investor protection on a national and international level.